2022
DOI: 10.1021/acs.jafc.2c05470
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cuticular Wax in Tea Plant and Its Modification in Response to Low Temperature

Abstract: Cuticular wax ubiquitously covers the outer layer of plants and protects them against various abiotic and biotic stresses. Nevertheless, the characteristics of cuticular wax and its role in cold resistance in tea plants remain unclear. In our study, cuticular wax from different tissues, cultivars, and leaves during different spatio-temporal growth stages were characterized and compared in tea plants. The composition, distribution pattern, and structural profile of cuticular wax showed considerable tissue speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The Clade 2 currently has only three characterized members (AtCER2, ZmGlossy2 and ZmGlossy2-like), all of which are associated with epicuticular waxes synthesis [ 3 ]. Epicuticular waxes are essential for plants to cope with environmental stresses [ 53 ]. Herein, we identified five members of the tea plant genome whose functions deserve further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The Clade 2 currently has only three characterized members (AtCER2, ZmGlossy2 and ZmGlossy2-like), all of which are associated with epicuticular waxes synthesis [ 3 ]. Epicuticular waxes are essential for plants to cope with environmental stresses [ 53 ]. Herein, we identified five members of the tea plant genome whose functions deserve further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research revealed that trichome density and stomata density were possible contributors to willow rust resistance (Crowell et al, 2020). Wax was a class of secondary metabolites that evolved during the long-term ecological adaptation of plants and was widely involved in plant responses to biotic stress and abiotic physiological processes Zhu et al, 2022). Plant secondary metabolites were the chemical defense factors of plants against pathogen infection and there were many types of them.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we have determined the concentration of biochemical markers such as photosynthetic pigments (chlorophyll a and b , carotenoids) and proline phytohormone. These pigments are relevant to adjust the response of plants toward stress environments and their relative concentration in leaves may vary in response to drought, salinity, or warm conditions. ,– The amino acid proline is an endogenous phytohormone known for its functions as osmotic regulator and membrane protection factor, functions that are of much relevance when seed germination and plant growth occur in drought and salinity conditions. Herein, the analysis of these biomarkers in the leaves of young plants has served to prove that plasma metabolic changes are responsible for the improvement of germination rate and the state of plants in their initial stages of growth. In addition, using a luminescent reagent, we have determined the differences in ROS concentration existing in the control and plasma-treated seeds.…”
Section: Introductionmentioning
confidence: 99%
“…These pigments are relevant to adjust the response of plants toward stress environments and their relative concentration in leaves may vary in response to drought, salinity, or warm conditions. 28 , 42 – 50 The amino acid proline is an endogenous phytohormone known for its functions as osmotic regulator and membrane protection factor, functions that are of much relevance when seed germination and plant growth occur in drought and salinity conditions. 51 57 Herein, the analysis of these biomarkers in the leaves of young plants has served to prove that plasma metabolic changes are responsible for the improvement of germination rate and the state of plants in their initial stages of growth.…”
Section: Introductionmentioning
confidence: 99%